Evaluation of smokers with and without asthma in terms of smoking cessation outcome, nicotine withdrawal symptoms, and craving: Findings from a self-guided quit attempt. (December 2016) - McLeish, Alison C.; Farris, Samantha G.; Johnson, Adrienne L.; Bernstein, Jonathan A.; Zvolensky, Michael J.
Abstract: Introduction: The aim of the current study was to evaluate smoking cessation outcome, nicotine withdrawal symptoms, and craving between smokers with ( n  = 47; 46.8% male, M age  = 40.0 years, SD  = 11.7) and without ( n  = 45; 51.1% male, M age  = 37.5 years, SD  = 11.1) asthma during a self-guided quit attempt. Methods: After completing a baseline assessment visit, participants attended study sessions on their scheduled quit day as well as follow-up visits (3 days, 7 days, 14 days, and 28 days) after their quit day. Results: Smokers with and without asthma did not differ in abstinence rates, smoking lapse, and rate of change in urge to smoke to reduce negative affect. However, smokers with asthma demonstrated a slower rate of decline in nicotine withdrawal symptoms and craving over time. Conclusions: These findings suggest that smokers with asthma may benefit from specialized smoking cessation treatments to address prolonged withdrawal symptoms and craving. Highlights: Smokers with and without asthma were compared during a self-guided quit attempt. There were no group differences in abstinence rates or likelihood of smoking lapse. Smokers with asthma had a slower rate of decline in nicotine withdrawal and craving.